2018
DOI: 10.1038/s41598-018-27480-4
|View full text |Cite
|
Sign up to set email alerts
|

Foveal Crowding Resolved

Abstract: Crowding is the substantial interference of neighboring items on target identification. Crowding with letter stimuli has been studied primarily in the visual periphery, with conflicting results for foveal stimuli. While a cortical locus for peripheral crowding is well established (with a large spatial extent up to half of the target eccentricity), disentangling the contributing factors in the fovea is more challenging due to optical limitations. Here, we used adaptive optics (AO) to overcome ocular aberrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 59 publications
(113 reference statements)
5
54
0
Order By: Relevance
“…A first step in introducing detection speed to test central crowding could be to flank the central target in combination with unflanked peripheral targets. Most challenging would still be to assess the limits of crowding on an arcminute scale due to optical limitation, such as irregularities in the cornea and lens blurring foveal vision (Coates et al, 2018). Such an approach would require a far more accurate eyetracking system because the resolution of the presently used remote infrared eye-tracker system would be too low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A first step in introducing detection speed to test central crowding could be to flank the central target in combination with unflanked peripheral targets. Most challenging would still be to assess the limits of crowding on an arcminute scale due to optical limitation, such as irregularities in the cornea and lens blurring foveal vision (Coates et al, 2018). Such an approach would require a far more accurate eyetracking system because the resolution of the presently used remote infrared eye-tracker system would be too low.…”
Section: Discussionmentioning
confidence: 99%
“…shown for opposite-contrast stimuli (Hess, Dakin, & Kapoor, 2000). Others have reported that foveal crowding occurs over very small distances but that sophisticated techniques are required to overcome the optical limitations (Siderov, Waugh, & Bedell, 2013;Coates, Levi, Touch, & Sabesan, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Now does critical target-flanker gap size, with increasing target eccentricity, increase linearly from there (as would be expected from Bouma's law) or does it first behave differently for a few minutes of arc, and then increase ( Figure 6c)? The hockey stick 21 Coates et al (2018) also isolate a separate recovery mechanism, first observed by Flom et al, 1963, at even smaller distances -0.5-0.75 arcminutes -that can be left aside for the present discussion. 22 The kink in the hockey stick is at s=5'.…”
Section: Crowding and Peripheral Visionmentioning
confidence: 81%
“…There is agreement that the interaction effect of foveal acuity targets, measured with conventional techniques, occurs "within a fixed angular zone of a few min arc" (3'-6') (Siderov, Waugh, & Bedell, 2013;Siderov et al, 2014, p. 147). However, a new study using adaptive optics (Coates et al, 2018) shows critical spacings are indeed even much smaller and only about a quarter of that range, 0.75 to 1.3 arcminutes edge-to-edge. 19 H. Wässle, personal communication 8/2019; there is no precise border so estimates vary widely.…”
Section: Crowding and Peripheral Visionmentioning
confidence: 98%
See 1 more Smart Citation